Process engineering in the food industry: Vol.1 - Developments and opportunities (London, 1989)
The book presents a new process that avoids axcessive temperature gradients and allows large pieces of meat to be sterilised without overcookong, including extrusion cooking and ready-meal production. It advocates a systematic approach to the study and modelling of food fouling, and it continues with a comparison of two possible fouling monitors. It indicates that up to two-thirds of design time will be concerned with cleaning and disinfection processes, offers practical advice on design with due regard to hygiene, deals with microprocessor control of clean-in-place systems, which are an essential prerequisite of modern food processing plant. In the chemical industry this is achieved by widespread feedback control loops. Thus, subtle variations in processing are required if a uniform specification product is to be obtained. It is thereforedesirable for sensors to detect the state of food in the middle of the processing in order to allow control adjustments to be made on-line. For this reason details of work on two novel sensors are discussed. The book concludes with a section on membrane separation which is already a commercial success in certain areas of the food industry
Keywords: food processing,food industry and trade